Mason Wasps of Florida, Zethus spp. (Insecta: Hymenoptera: Vespidae: Eumeninae) - E. E. Grissell (EDIS, 2007)
EENY-402, a 3-page illustrated fact sheet by E. E. Grissell, is part of the Featured Creatures Collection. It describes these wasps who make their nests in twigs and branches and old insect burrows in south Florida, their distribution, identification, biology, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, May 2007.